Adaptive synchronization of chaotic CNN and applications to secure communication. - Phương, Đàm Thanh; Cát, Phạm Thượng (Journal of Computer Science and Cybernetics, 2013)
This paper solves chaotic signal synchronization problem of a cellular neural network with unknown parameters by using adaptive control theory. The constructed control and the parameters update laws are proven to ensure the global synchronization based on Lyapunov stability theory. From this result, we bring out the secure communication model for the synchronization and the chaotic property of the cellular neural network (SC-CNN). The simulation results are performed on Matlab.